Lithospheric fault and kinematic decoupling of the Apennines system across the Pollino range. Issue 7 (13th April 2016) - Chiarabba, Claudio; Agostinetti, Nicola Piana; Bianchi, Irene
Abstract: A persistent seismic gap is hypothesized in the Pollino area (southern Italy), at the boundary between the Apennines and the Calabrian arc. Presently, seismic swarms are active in the gap area, creating concerns for possible future large earthquakes. In this study, we model the deep Earth structure across the Pollino range to give new insights on the kinematics and tectonics of this enigmatic area. Migrated receiver function profiles show a subvertical lithospheric discontinuity, delineated by an abrupt change in Moho depth and mantle fabrics across the range. The lithospheric‐scale discontinuity bounds the area of earthquake swarm activity and likely decouples the delamination‐related extension of the Apennines from the extensional collapse of the Calabrian fore arc. This large‐scale discontinuity implies that the normal faults are segmented across the range, limiting the lateral extent of faults where future earthquakes might occur. Key Points: A huge set of receiver functions is used to define a lithospheric fault at the Ionian slab edge The fault decouples the deformation of Apennines (delamination) from Calabrian forearc (retreat) The fault segments the normal fault system within the 60 km long Pollino seismic gap